Global m6A RNA and whole 5mC DNA methylation specifically contribute to cell replicative and premature senescence induced by extrinsic oxidative stress - Chenyu Zhu; Tingting Huang; Jiaqi Fu; Min Li; Luyi Tan; Xinyu Zhang; Wenli Cheng; Caiyun Lai; Zhangying Wang; Wenji Zhang; Wenjuan Zhang (mSystems)
ABSTRACT Hydrogen peroxide (H2O2) is a typical representative substance of environmental oxidative stress. Exogenous substances can alter epigenetic modifications from the DNA to the RNA level through oxidative stress. We investigated methylation profiles of whole RNA m6A and DNA 5mC in the epitranscriptome and epigenome of human lung embryonic fibroblasts in replicative senescence and H2O2-induced premature senescence. By RNA-seq, the expression of most RNA m6A and DNA 5mC regulators was reduced in both replicative and premature senescence respectively, whereas the expression of most senescence-associated secretory phenotypes, such as SASP, was increased in premature senescence. MeRIP-seq revealed that RNA m6A methylation sites were relatively conserved in replicative and premature senescence, but that premature senescence had higher levels of m6A methylation than replicative senescence. MeDIP-seq results showed that 5mC methylation was higher in replicative senescence than in premature senescence, and the methylation peak with the largest difference appeared on chromosome 19. DO enrichment analysis indicated that RNA m6A methylation played a key role in malignant tumor regulation in replicative senescence, whereas DNA 5mC promoted malignant tumor in premature senescence. Next, to explore the interaction of RNA m6A and DNA 5mC in the senescent state, we screened common hub genes for replicative and premature senescence. Four m6A-modified target genes, namely, ASPM, CENPF, MKI67, and BLM, were all closely associated with mitosis and cell cycle regulation. In addition, we also screened 5mC target genes including CDC45, TPX2, and UBE2T.IMPORTANCERNA-seq showed that most of the m6A and 5mC regulators and the majority of SASP expression were downregulated. The m6A motif was conserved in replicative and premature senescence, and its methylation was higher in replicative senescence. The most differentially 5mC methylation peak was located on chromosome 19, and its methylation was higher in premature senescence. Gene regulation by m6A in replicative senescence and 5mC in premature senescence was enriched in malignant tumors.